Even if everything ends - Liljestrand, Jens, 1974- (Scout Press, 2023)
Follows a middle aged media consultant, a twenty-something influencer and regretful climate change denier, and a teenager with a personal vendetta as they all struggle to survive in a world lit on fire and full of refugees due to escalating climate crises.